Islamic sensory history. (Leiden, Boston)
xxii, 593 sayfa
Keywords: ''Islamic Sensory History, Volume 2 : 600-1500 is composed of selected texts translated into English from their original languages. The selections are short texts, or excerpts from longer texts, chosen by the editors and contributors for their illustrative and interesting engagements with issues related to the senses and the sensory in different times, places, and social milieus throughout the history of Islamic societies. Each selection is prefaced by a short introductory essay by the translator on the text and its author, with specific attention to and commentary upon the importance or role of the senses in this text's language, genre, and social context.'' --